(untitled) (Research, Society and Development, 2020)
In order to evaluate the effect of humectant additives on the microbiological and physical-chemical quality during the shelf life of sheep meat, six treatments were developed using lactic acid, sodium lactate, sodium tripolyphosphate and combinations of sodium lactate with tripolyphosphate sodium and lactic acid with sodium tripolyphosphate, in addition to control. The samples were immersed for 15 minutes in solutions with the concentrations of 5% LS, 5% AL, 5% TPF, 2.5% sodium lactate + 2.5% sodium tripolyphosphate (LSTPF), 2.5% lactic acid + 2.5% sodium tripolyphosphate (ALTPF) and the control sample. For the physical and microbiological analyzes, the sheep meat samples were analyzed in the storage times: 0, 3, 6, 9 and 12 days (4ºC ± 1º), with subsequent times starting from day zero, they were submitted to the pH, PPC, CRA, L *, a *, b * and FC tests and the total count of mesophilic aerobic and psychrotrophic bacteria. The treatments with sodium lactate were efficient in maintaining characteristics such as pH and color, being the association between sodium lactate and sodium tripolyphosphate more effective in regulating these parameters. The ALTPF treatment showed positive results regarding pH and CRA. The additives had a positive influence on lipid oxidation. Regarding microbiological quality, the additives were not efficient due to the initial contamination.